2022
DOI: 10.3389/fneur.2021.786166
|View full text |Cite
|
Sign up to set email alerts
|

Non-motor Adverse Effects Avoided by Directional Stimulation in Parkinson's Disease: A Case Report

Abstract: IntroductionDeep brain stimulation (DBS) is widely used for treatment of advanced, medication-refractory Parkinson's disease (PD). However, a significant proportion of patients may suffer adverse effects; up to 10% will present one or more transient or permanent neurobehavioral events.Patient and MethodsIn our case study, a 44-year-old woman diagnosed with PD 6 years previously who was suffering from motor fluctuations, dyskinesia, and freezing of gait episodes was submitted for DBS and implanted with directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…For globus pallidus internus (GPi) DBS, mental status/behavioral changes are also the highest reported followed by speech disturbances (10). Complications can be further derived from stimulation, such as electrical flow expanding through association regions and causing non-motor symptoms including laughter and hypomania (11).…”
Section: Discussionmentioning
confidence: 99%
“…For globus pallidus internus (GPi) DBS, mental status/behavioral changes are also the highest reported followed by speech disturbances (10). Complications can be further derived from stimulation, such as electrical flow expanding through association regions and causing non-motor symptoms including laughter and hypomania (11).…”
Section: Discussionmentioning
confidence: 99%
“…6 Neuropsychiatric effects of STN-DBS include potential worsening of depression and anxiety and impulse control disorders. 12 Despite stable improvements in global outcomes of DBS, patients can have worsening of gait impairment and speech disturbances, as well as persistent levodopa-resistant freezing of gait. 13 Overall, many studies show that no significant differences are found in long-term control of motor symptoms between the two sites.…”
Section: Commentmentioning
confidence: 99%
“…The STN target is thought to be associated with increased medication reduction compared with the globus pallidus internus (GPi) target, while the GPi target is thought to be better at addressing dyskinesias 6 . Neuropsychiatric effects of STN-DBS include potential worsening of depression and anxiety and impulse control disorders 12 . Despite stable improvements in global outcomes of DBS, patients can have worsening of gait impairment and speech disturbances, as well as persistent levodopa-resistant freezing of gait 13 .…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…Especially since the advent of directional leads, contact selection can be employed for selective current distribution to improve stimulation response [6][7][8]. Consequently, the practice of meticulously testing acute stimulation effects for each contact to determine optimal stimulation response, the monopolar review (MPR), has become even more tedious and time-consuming.…”
Section: Introductionmentioning
confidence: 99%